2013
DOI: 10.1016/j.seizure.2013.04.012
|View full text |Cite
|
Sign up to set email alerts
|

Etiologies of epilepsy and health-seeking itinerary of patients with epilepsy in a resource poor setting: Analysis of 342 Nigerian Africans

Abstract: This study showed the pattern of causes of epilepsy in Nigerian Africans. The health seeking behavior and itinerary of the PWE revealed a preference for traditional healers. There is need for health policies and epilepsy awareness campaigns to prevent causes of seizures and improve the knowledge of the public respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 16 publications
3
15
3
Order By: Relevance
“…The majority of PLWE in this sample did not know the cause of epilepsy and the associated precipitating factors. Our finding is consistent with earlier studies on epilepsy knowledge and attitudes in Uganda and other similar settings in Africa (4,(18)(19)(20). Having the right knowledge, attitudes and resources to provide adequate epilepsy management in PLWE and their caregivers' influences the preferred choice of care either traditional healers or mainstream medicine.…”
Section: Individual Factorssupporting
confidence: 93%
“…The majority of PLWE in this sample did not know the cause of epilepsy and the associated precipitating factors. Our finding is consistent with earlier studies on epilepsy knowledge and attitudes in Uganda and other similar settings in Africa (4,(18)(19)(20). Having the right knowledge, attitudes and resources to provide adequate epilepsy management in PLWE and their caregivers' influences the preferred choice of care either traditional healers or mainstream medicine.…”
Section: Individual Factorssupporting
confidence: 93%
“…The majority of PLWE in this sample did not know the cause of epilepsy and the associated precipitating factors. Our finding is consistent with earlier studies on epilepsy knowledge and attitudes in Uganda and other similar settings in Africa ADDIN EN.CITE (4,(18)(19)(20) . Interpersonal and social support networks.…”
Section: Individual Factorssupporting
confidence: 93%
“…Although these studies have identified numerous risk factors associated with epilepsy, the results were highly variable. While stroke and head injury have been implicated as factors for adults from high-income countries (Guekht et al, 2010;Pi et al, 2014), epilepsy was associated with parasitic diseases, perinatal insults and central nervous system (CNS) infections in developing countries (Ogunrin et al, 2013;Asadi-Pooya and Hojabri, 2005;Osakwe et al, 2014).…”
Section: Introductionmentioning
confidence: 99%